The Moderating Influence Of Gender Bias On Factors Determining Choice Of Successor In South African Family-Owned Businesses - Maphalala, Siyabonga Mthunzi (University of the Witwatersrand, Johannesburg, 2025)
Family businesses play a crucial role in South Africa’s economy, contributing to job creation and growth. However, patriarchal norms often favour male successors over equally qualified female family members, creating challenges in equitable succession planning. This study explores how gender bias moderates the relationships between succession determinants: successor preparation, planning-control activities, cultural-family dynamics and succession outcomes. Guided by Human Capital Theory and Gender Theories, the study employed a quantitative, cross-sectional design. Data was collected via structured online questionnaires from stakeholders in family-owned businesses across South Africa. Stratified random sampling ensured geographic diversity, and regression and moderation analyses were conducted using IBM SPSS Statistics. The findings reveal that gender bias weakens the positive effects of succession planning efforts. Patriarchal stereotypes often limit opportunities for female successors, despite their qualifications. However, businesses with inclusive practices like gender-neutral policies, experience smoother leadership transitions and greater sustainability. This study contributes to Human Capital Theory by showing how gender bias limits leadership development and extends Gender Theories by illustrating how cultural norms shape succession outcomes in South African family businesses.
A research report submitted in fulfillment of the requirements for the Master of Management in Entrepreneurship and New Venture Creation, in the Faculty of Commerce Law and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2025
Keywords: UCTD; Family business; Succession planning; Cultural-family dynamics; SDG-5: Gender equality; SDG-8: Decent work and economic growth